2001
DOI: 10.1097/00001888-200111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

How a Teaching Hospital Implemented Its Termination Policies for Disruptive Residents

Abstract: The development of Policy Standards for Termination that both protect and support residents while safeguarding sponsoring institutions has become increasingly necessary. To date, however, there has been little in the literature that discusses policies that have undergone thorough testing to the highest levels of the U.S. judicial system. Berkshire Medical Center (BMC), an acute-care community teaching hospital affiliated with the University of Massachusetts Medical School, developed a set of specific policies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The 'failure to fail' literature, a body of work exploring the perceived barriers to accurately grading learners who do not meet academic benchmarks, makes it clear that there are contextual, personal and student-centred variables that play a role in faculty members' decision making about students. [12][13][14][15][16][17][18][19][20] For example, Luhanga et al found that preceptors considered learners' debt and proximity to graduation when deciding whether or not to submit a failing grade. 16 One goal of this study was to explore which particular student-centred elements most inform and influence committee members' decision making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 'failure to fail' literature, a body of work exploring the perceived barriers to accurately grading learners who do not meet academic benchmarks, makes it clear that there are contextual, personal and student-centred variables that play a role in faculty members' decision making about students. [12][13][14][15][16][17][18][19][20] For example, Luhanga et al found that preceptors considered learners' debt and proximity to graduation when deciding whether or not to submit a failing grade. 16 One goal of this study was to explore which particular student-centred elements most inform and influence committee members' decision making.…”
Section: Discussionmentioning
confidence: 99%
“…The mean student debt for that same year was $180 723. Given these circumstances, dismissal from medical school can have an enormous emotional, financial and professional impact on the lives of medical students …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] Before a remediation plan can be developed, every effort needs to be made to ensure that the correct underlying problem, deficiency, or performance issue is identified. Poor performance can have confounding or contributing factors such as stress at home, substance abuse, cognitive issues related to language or processing issues, etc.…”
Section: Development and Monitoring Of The Remediation Planmentioning
confidence: 99%
“…Thorough documentation of all issues related to problem residents is also critical. 4 JGIM welcomes your letters and comments. Letters may contain brief commentaries on articles published in the Journal, illustrative case reports, general suggestions for improving the Journal, or other information of interest to readers.…”
mentioning
confidence: 94%